Alternativas en el manejo de materiales no convencionales aplicables en la construcción de la vivienda social en Palmira Valle del Cauca. Caso de estudio concreto celular. (2022)
This research was carried out with the purpose of demonstrating the use of materials unconventional in the social housing of Palmira, Valle del Cauca, in order to improve finishes, reduce the contaminant footprint and costs in them, aspects were addressed historical, social, cultural and environmental, without neglecting all the aspects crucial for this research.